Grey water treatment through a built waterlogged system - Oliveira, Danielle Martins Cassiano de; Peralta, Aline Hanny; Cardoso, Mariane Libório; Costanzi, Ricardo Nagamine (Revista Hipótese, 2015)
Actually, the protection of water resources has become a priority for society, due to its scarcity and its importance to the maintenance of life. Some wastewater treatments can be used to enable water reuse. Wetland Constructed wetland systems (CWS) is a process to enable reuse. Wetlands are a low cost, both for operation and the maintenance. Wetlands are effective in removing impurities. The objective of this study is to analyze the efficiency of a horizontal subsurface flow CWS followed by a vertical flow CWS for the treatment of greywater from washing machine. The greywater was inserted into the system by a reservoir which supplies the CWS treatment system. Parameters of pH, turbidity, conductivity, apparent color, total solids, volatile solids, suspended solids and chemical oxygen demand (COD) were analyzed. The results show an efficiency greater than 90% for apparent color, turbidity and COD.
Keywords: Constructed Wetlands Systems; Greywater; Wastewater; Reuse